Comparison Of The S Curve With The CPM Method In Analyzing Project Scheduling - Alfonsus Fung Abimanyu Wicaksono; I Nyoman Dita Pahang Putra (International Journal of Industrial Innovation and Mechanical Engineering, 2024)
Project management is managing projects by considering all aspects of construction projects. A project must run according to plan and can be completed on time, so planning is needed before a project runs; scheduling must be considered. Scheduling is an important step in determining the exact duration and sequence for each activity in the project to create a logically structured schedule that can be implemented realistically. Many methods can be applied in project scheduling, such as S Curve and CPM (Critical Path Method). The use of different scheduling methods is considered to affect the final result of scheduling. Therefore, it is necessary to analyze the two methods. The analysis was carried out by comparing the critical trajectory, duration, and cost of structural work on the Kediri Regency Stadium Design and Build Project produced by the two methods so that it can be concluded which method is more efficient. The results showed differences in critical trajectories in the S curve and the CPM methods. In addition, the difference in duration is obtained; the S curve method requires a work duration of 140 days with a cost of Rp 48,041,965,577.96. Meanwhile, the CPM method requires a work duration of 131 days at a cost of Rp 47,535,997,308.05. Based on the results, the CPM method is superior in terms of time and cost.